Influences of Hydrodynamic Forces on the Identification of the Rotor-Stator-Rubbing Fault in a Rotating Machinery - Bernard Xavier Tchomeni; Desejo Filipeson Sozinando; Alfayo Alugongo (International Journal of Rotating Machinery)
Mechanical failures of a complex machine such as rotor widely used in severe conditions often require specialized knowledge, technical expertise, and imagination to prevent its rupture. In this paper, a model for analyzing excitation of a coupled lateral-torsional vibrations of a shaft system in an inviscid fluid is proposed. The model considers the recurrent contact of the vibrating shaft to a fixed stator. The simplified mathematical model of the rotor-stator system is established based on the energy principle. The dynamic characteristics of the fluid-rotor system are studied, and the features of rub-impact are extracted numerically and validated experimentally under the effects of the unbalance and the hydrodynamic forces. The main contribution of this article is in extraction and identification of the rub features in an inviscid medium which proved to be complex by the obstruction of the fluid and required the use of appropriate signal processing tools. The results through a synchrosqueezing wavelet transform indicated that the exciting fluid force could significantly attenuate the instability and amplitude of rubbing rotor. The experimental results demonstrated that for half the first critical speed, the subharmonic 1/2×Ω and the irregular orbit patterns provide good indices for rub detection in an inviscid fluid of the rotating shafts. Finally, it is revealed that the instantaneous frequency extraction based on wavelet synchrosqueezing is a useful tool to identify the weak and hidden peak harmonics localised in the time-frequency maps of the fluid-rotor system.